A Review on Honey Adulteration and the Available Detection Approaches - Jaafar, M. B.; Othman, M. B.; Yaacob, M.; Talip, B. A.; Ilyas, M. A.; Ngajikin, N. H.; Fauzi, N. A. M. (International Journal of Integrated Engineering, 2020)
Over the last few decades, the utilization of stingless bees honey product grew significantly due to its natural therapeutic value in honey. These make the demand for honey rises and tends to have a lot of honey product available in the commercial market. However, the purity of honey can be sceptical whenever it turns up to be added or removed with different substances. Recently, adulteration of honey becomes a complex issue because the highly sophisticated adulteration procedures are continually being evolved and the legislative determination of honey quality indicator is incapable to identify most honey adulteration procedures. Therefore, a comprehensive overview of the method of adulterated honey, including direct and indirect adulteration are discussed in this paper. In addition to this, the detection methods approached by most researchers are briefly explained. All these methods contribute to the knowledge about each aspect of honey authenticity and give beneficial information in oncoming works.